English or Indonesian Language? Parents’ Perception Toward Children's Second Language Learning Context - Nihta Vera Frelly Liando; Devilito Prasetyo Tatipang (Jurnal Lingua Idea, 2022)
The phenomenon of teaching English and Indonesian language, especially in North Sulawesi, as a second language overlaps, where some argue that teaching Indonesian language should come first so that children will not forget Indonesian language or, in other words, children will master their national language. In this study, the method used is a descriptive method with a qualitative approach. The sample used as respondents by the researcher is parents in North Sulawesi who have children who can speak English and Indonesian, in addition, to their mother tongue (Manado language/Regional language), and the respondents consisted of 10 parents. The researcher used questionnaires to gather parents' perceptions of whether the children should be taught English or Indonesian Language first. However, some people think teaching English is very important because mastering English as an international language is necessary. English is suitable for children as their second language, but teaching Indonesian language as the national language is also very important. Therefore teaching between these two languages must be balanced so that it does not only English that can be mastered by children or not only Indonesian language.